INTEGRASI PROJECT-BASED LEARNING DALAM PEMBELAJARAN INTERAKSI MANUSIA DAN KOMPUTER DI PROGRAM STUDI SISTEM INFORMASI: Human-Computer Interaction, learning outcomes, Project-Based Learning, student creativity, UI/UX. - Abidin, Zainil; Hutabarat, Benedika Ferdian; Rabiula, Andre (JURNAL AKADEMIKA, 2025)
This study aims to analyze the effect of implementing the Project-Based Learning (PjBL) model on student learning outcomes and task creativity in the Human-Computer Interaction course. The research method used is quantitative with a quasi-experimental design. The research subjects consisted of two classes: a control class using conventional methods and an experimental class applying PjBL. Data were collected through final exam tests and a rubric-based assessment of UI/UX project creativity. The analysis results showed that the PjBL class achieved significantly higher scores in both final exams and task creativity (p < 0.05). It is concluded that the PjBL model is effective in enhancing students' understanding and UI/UX design skills in the Information Systems program.